Circadian BMAL1 regulates mandibular condyle development by hedgehog pathway. (20th November 2019) - Yu, Shaoling; Tang, Qingming; Xie, Mengru; Zhou, Xin; Long, Yanlin; Xie, Yanling; Guo, Fengyuan; Chen, Lili
Abstract: Objective: Chondrogenesis and endochondral ossification in mandibular condyle play crucial roles in maxillofacial morphogenesis and function. Circadian regulator brain and muscle arnt‐like 1 (BMAL1) is proven to be essential for embryonic and postnatal development. The goal of this study was to define the functions of BMAL1 in the embryonic and postnatal growth of mandibular condylar cartilages (MCC). Materials and Methods: Micro‐CT, TUNEL staining and EdU assay were performed using BMAL1‐deficient mice model, and in vitro experiments were performed using rat chondrocytes isolated from MCC. RNA sequencing in mandibular condyle tissues from Bmal1 ‐/‐ mice and the age‐matched wild‐type mice was used for transcriptional profiling at different postnatal stages. Results: The expression levels of BMAL1 decrease gradually in MCC. BMAL1 is proved to regulate sequential chondrocyte differentiation, and its deficiency can result in the impairment of endochondral ossification of MCC. RNA sequencing reveals hedgehog signalling pathway is the potential target of BMAL1. BMAL1 regulates hedgehog signalling and affects its downstream cascades through directly binding to the promoters of Ptch1 and Ihh, modulating targets of hedgehog signalling which is indispensable for endochondral ossification. Importantly, the short stature phenotypes caused by BMAL1 deficiency can be rescued by hedgehog signalling activator. Conclusions: Collectively, these results indicate that BMAL1 plays critical roles on chondrogenesis and endochondral ossification of MCC, giving a new insight on potential therapeutic strategies for facial dysmorphism.